“Take a step back”: teacher strategies for managing heightened emotions - Beltman, Susan; Poulton, Emily (SPRINGER, 2019)
© 2019, The Australian Association for Research in Education, Inc. From a social ecological perspective, there are multiple challenges that can lead to stress, burnout and attrition in teachers and school leaders. The capacity to manage negative emotions is important for emotion regulation, emotional intelligence, coping and mindfulness. Emotions also form one dimension of resilience as teachers use strategies to maintain their commitment and well-being. This paper examines those strategies nominated by 73 practicing teachers who completed online modules designed to enhance resilience capacity. An iterative process of coding of 206 separate responses led to 14 first-order categories. These were then coded into four higher-order categories of Waiting, Assessing, Problem-Solving and Being Proactive. The largest group of responses, aligned with mindfulness approaches, referred to the need to take a break to calm oneself and manage the emotions, before assessing the situation and engaging in direct problem-focused strategies. Participants also reported putting proactive strategies in place. Implications for teacher professional learning are discussed including the challenge of focusing on individual capacity when the source of challenges may lie in wider policies or workplace structure. Limitations include lack of corroborating observational data, and suggestions are made for further research to understand how teachers manage the emotional challenges of their work.